The Effect of Production and Sales Costs on Net Profit of Micro, Small and Medium Business in Bulukumba District (Case Study of Marning Corn Production MSMEs) - Nasrullah; Andi Rustam; Sultan Sarda; Mutmainna; Irpan (IECON: International Economics and Business Conference, 2023)
The analysis techniques in this study are validity test, reliability test, classic assumption test, multiple linear regression analysis test and hypothesis testing through determination test and t (partial) test. The results of this study indicate that partially Production Costs have a positive and significant effect on Net Income (Study on Micro, Small and Medium Enterprises Cases in Bulukumba Regency) as indicated by a calculated T value of 3.498 > Table T value of 2.04523 and a significance value of 0.002 < 0. 05. Sales have a positive and significant effect on net income (Study on Micro, Small and Medium Enterprises in Bulukumba Regency) as indicated by a calculated T value of 2.692 > Table T value of 2.04523 and a significance value of 0.012 < 0.05.